Neuroimaging and molecular mechanism of action of Cang-ai volatile oil in the treatment of vascular cognitive impairment - Chen, Bojun; Liang, Boshen; Li, Wei; Wang, Lei; Wang, Jiaojian; Xiong, Lei; Gao, Fabao (Frontiers in Neuroscience, 2025)
BackgroundCangai volatile oil (CAVO), as a traditional Chinese medicinal volatile oil, has been applied for its neuroprotective effects in conditions such as depression.ObjectiveTo investigate whether CAVO can improve brain cognitive function in rats with vascular cognitive impairment using 7T high-field functional magnetic resonance imaging and molecular biology.MethodCAVO treatment was administered in a rat model of vascular dementia induced by bilateral permanent occlusion of the common carotid arteries (2 VO). The water maze was employed for behavioral assessment, while magnetic resonance imaging examined alterations in local homogeneity, low-frequency amplitude, and functional connectivity within the rat brain. Protein expression of inflammatory factors (NLRP3), apoptotic proteins (BAX, Bcl-2), and endoplasmic reticulum stress proteins (CHOP, PERK, GRP78) in the rat hippocampus was analyzed using Western blotting and PCR.ResultsCAVO enhances functional connectivity strength in regions including the cingulate cortex-piriform cortex and anterior cingulate cortex-hypothalamus in VCI rats (p < 0.05). Simultaneously, CAVO reduced the expression of proteins in the endoplasmic reticulum stress pathway (CHOP, pPERK, CHOP, GRP78), the inflammatory factor NLRP3, and the apoptosis pathway (BAX, Bcl-2, Caspase3) (p < 0.05), increased Bcl-2 protein expression (p < 0.05). It also significantly reduced the mRNA expression of CHOP, NLRP3, GRP78, and BAX (p < 0.01).ConclusionThis study demonstrates that CAVO therapy reduces inflammatory responses in brain regions of VCI rats, decreases apoptosis and necrosis, protects neurons in affected areas, and simultaneously enhances functional connectivity strength between brain regions in VCI rats, thereby exerting a cognitive-improving effect on VCI.